Contest-Driven Soft-Robotics Boost: The RoboSoft Grand Challenge - Calisti, Marcello; Cianchetti, Matteo; Manti, Mariangela; Corucci, Francesco; Laschi, Cecilia (Frontiers in Robotics and AI, 2016)
This paper reports the design process, the implementation and the results of a novel robotic contest addressing soft robots, named RoboSoft Grand Challenge. Application-oriented tasks were proposed in three different scenarios where soft robotics is particularly lively: manipulation, terrestrial and underwater locomotion. Starting from about sixty expressions of interest submitted by international teams distributed across the world, nineteen robots were eventually selected to participate in the challenge in two of the initially proposed scenarios, i.e. manipulation and terrestrial locomotion. Results highlight both the effectiveness and limitations of state of the art soft robots with respect to the selected tasks. The paper will also focus on some of the advantages and disadvantages of contests as technology-steering mechanisms, including what we called “reductionist design”, a phenomenon in which simplistic solutions are devised to purposely tackle the proposed tasks, possibly hindering more general and desired technological advancements.